2018
DOI: 10.1038/s41598-018-35106-y
|View full text |Cite
|
Sign up to set email alerts
|

ME1 promotes basal-like breast cancer progression and associates with poor prognosis

Abstract: Basal-like breast cancer (BLBC) is associated with a poor clinical outcome due to the few treatment options and absence of effective targeted agents. Here, we show that malic enzyme 1 (ME1) is dramatically upregulated in BLBC due to ME1 copy number amplification. ME1 expression increases glucose uptake and lactate production, and reduces oxygen consumption, leading to aerobic glycolysis. ME1 expression promotes, whereas knockdown of ME1 expression suppresses tumorigenicity. In breast cancer patients, ME1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 36 publications
5
34
0
Order By: Relevance
“…Previous study of ME1 in breast cancer only focusing on TNBC subtype drew the same conclusion as ours that ME1 was highly expressed in TNBC cells, 14 but its upstream upregulators have not been reported yet. We also found the relationship between ME1 expression and HER2 positive in Curtis Breast Dataset.…”
Section: Discussionsupporting
confidence: 72%
“…Previous study of ME1 in breast cancer only focusing on TNBC subtype drew the same conclusion as ours that ME1 was highly expressed in TNBC cells, 14 but its upstream upregulators have not been reported yet. We also found the relationship between ME1 expression and HER2 positive in Curtis Breast Dataset.…”
Section: Discussionsupporting
confidence: 72%
“…Previous study of ME1 in breast cancer only focusing on TNBC subtype drew the same conclusion as ours that ME1 was high expressed in TNBC cells (15), but its upstream up-regulators have not been reported yet. We also found the relationship between ME1 expression and HER2 positive in Curtis Breast Dataset.…”
Section: Discussionsupporting
confidence: 74%
“…Although ME1 is reported to enhance cell proliferation and metastasis capacity in multiple cancer types (10,11,15,17), the underlying mechanism of which still remains inexplicit. On one hand, ME1 catalyzes malate to pyruvate, inducing cell glucose uptake and lactate production and thus promote Warburg effect, which is favorable for tumor (15) As far as we know, there is still no anti-tumor drugs targeting ME1. Considering the important role of ME1 in tumor progression, we also reflect on whether ME1 is a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Nrf2 is involved in the expression of antiapoptotic proteins, promotes chemotherapy tolerance of liver cancer, and is associated with the expression of Bcl-xl, an antiapoptotic gene [35]. In addition, it has been observed that ME1 expression is positively correlated with larger tumour size, higher grade, poorer survival, and chemotherapy resistance in breast cancer patients [36]. In the present study, knockdown of Keap1 under fasting conditions resulted in enhanced cell viability, the inhibition of apoptosis and ROS accumulation, and increased expression of Nrf2/ARE signalling pathway components ( Supplementary Figures S1A-C).…”
Section: Discussionmentioning
confidence: 99%